On the unique solvability of a non‐local boundary value problem for linear functional differential equations - Rontó, András; Pylypenko, Viktor; Dilna, Nataliya (Mathematical Modelling and Analysis, 2008)
General conditions are obtained for the unique solvability of a non‐local boundary value problem for systems of linear functional differential equations. First Published Online: 14 Oct 2010